The Effect of Investment Decisions on Firm Value with CSR and Profitability as Moderating Variables - Tedrick Soetedjo; Elsa Imelda (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the effect of investment decisions on firm value, with Corporate Social Responsibility (CSR) and profitability serving as moderating variables. The research sample consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, selected through purposive sampling based on predetermined criteria. The data used are secondary data derived from annual financial statements and sustainability reports obtained from the official IDX website. Data analysis is conducted using panel data regression with EViews software, and the best estimation model employed is the Fixed Effect Model (FEM). The results indicate that investment decisions proxied by the Price-to-Earnings Ratio (PER) do not have a significant effect on firm value proxied by Tobin's Q, suggesting that investment decisions have not become a primary indicator in assessing firm value in the energy sector. Furthermore, CSR measured using the Global Reporting Initiative (GRI) disclosure index does not significantly strengthen the relationship between investment decisions and firm value, indicating that CSR disclosure is not yet perceived as a strong signal by investors. In contrast, profitability proxied by Return on Equity (ROE) is found to significantly strengthen the effect of investment decisions on firm value, highlighting the role of profitability in reinforcing investment decision signals amid high earnings volatility in the energy sector.